Performance of Household Water Treatment Methods for Microbial Removal under Household Conditions in Kabale District, Uganda - Alex, Saturday; George Lukoye Makokha; Anthony Macharia (Omega Publishers, 2018)
Despite the Ugandan government efforts to improve access to safe water sources, the rate at which diseases spread as a result of unsafe drinking water is absolutely high. The purpose the study was to assess the performance of household water treatment methods (HWT) and evaluate their ability to improve the microbial quality of drinking water under household conditions in Kabale District. We randomly selected 205 households, where we collected treated and untreated water samples. We analyzed 46 paired samples (untreated and treated) of drinking water from 46 households that reported treated water available. Samples were analyzed for total coliforms and Escherichia coli, the major indicators of biological contamination of drinking water, to measure effectiveness of treatment under household conditions. All reported HWT did not significantly improve the microbial quality of drinking water. Mean log10 total coliforms removal were 0.7 log10 (40.1%) for boiling method, 0.2 log10 (23.7%) for biosand filtration method, -0.01log10 (-18.1%) for let it stand and settle method and 0.1 log10 (16%) for application of aqua safe tablets. In addition, mean log10 Escherichia coli removal were 0.7 log10 (-22.6) for boiling method, 0.3log10 (37.5%) for biosand filtration method, -0.4 log10 (-200%) for let it stand and settle method and 0.6 log10 (50%) for application of aqua safe. The microbiological quality of stored treated drinking water was significantly low. The government should sensitize the local people on safe storage of drinking water.